Structural, optical, antibacterial analysis of Se NPs synthesized by precipitation method. (24th September 2020) - Dar, Mohd Arif; Mala, Nazir Ahmad; Dar, G N; Satheesh Kumar, S; Govindarajan, D
Abstract: In this paper Se NPs have been synthesised through precipitation technique by using different sorts of solvents such as sodium hydroxide, tin chloride, sodium borohydride, hydrochloric acid and citrus acid so as to consider its antibacterial activities. These Se NPs are characterised by experimental techniques such as UV-Vis spectrophotometer, SEM, TEM, FT-IR, XRD, EDX and antibacterial activities. Powder XRD analysis reveals the hexagonal phase (HCP) of Se NPs with average particle size of 27 nm. SEM and TEM reveal agglomerated spherical images with spherical shape and EDX spectra of the pure Se NPs show the peaks of pure selenium. Maximum absorption occurs in the range of 200–400 nm with an energy band gap of 3.58 eV. Presence of different functional groups liable for the production and stability of the Se NPs was confirmed by FT-IR spectrum. The antibacterial activity was achieved against two Gram-negative microorganisms (Escherichia coli, Salmonella typhi) and two Gram-positive microorganisms (Staphylococcus aureus, Streptococcus epidermidis) .